Pengaruh latihan board taps with ball terhadap kemampuan under the basket shoot pada ekstrakulikuler bola basket putri SMPN 2 sikur tahun 2025 - Nila Hadiyatullah; Baiq Satrianingsih; Nazalus Syobri (Jurnal Pengetahuan dan Pendidikan, 2025)
Based on the results of observations conducted, it was found that the under-thebasket shooting skills of female students in the extracurricular basketball program at SMPN 2 Sikur still need improvement due to several factors, including a lack of exercise variety, limited facilities, and insufficient focus on specific skills. To address these issues, more effective and innovative training methods are required. One training method that can be applied is board taps with ball. This exercise aims to improve hand-eye coordination, reaction speed, and wrist strength, which are important aspects of under-the-basket shooting. This study was conducted as a quasi-experimental study with a one-group pretest and posttest design. Sampling was conducted using probability sampling (random sampling) with simple random sampling technique due to the population size exceeding 30. The sample for this study consisted of 7 individuals or 1 girls' basketball team from SMPN 2 Sikur. The instruments used to measure shooting ability included basketballs, whistles, and stopwatches. Data analysis technique: The Wilcoxon Signed Rank Test was used. Based on the t-test results, there was a significant difference between the under-the-basket shooting results before and after the treatment. he mean difference was -2.000. The t-value was -6.481 with degrees of freedom (df) = 6, and the significance value p < 0.001 (both one-sided and twosided), identifying that the difference was statistically significant. The 95% confidence interval range is from -2.755 to -1.245, so it can be concluded that board taps with ball exercises have a significant effect on improving the underthe-basket shooting ability of female students at SMPN 2 Sikur.